2013
DOI: 10.1002/ppul.22791
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic fluid stem cells protect rat lungs exposed to moderate hyperoxia

Abstract: Treatment with hAFS cells has a reparative potential through active involvement of cells in alveolarization and angiogenesis. A downstream paracrine action was also taken into account, in order to understand the immunodulatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…However, in this study, we found that in the late phase of BPD, a single dose of EPCs administered through the peripheral venous route only increased lung microvessels, with no improvement in alveolar structure as determined by RAC measurements. Compared with the two previous studies (9,10), the reason why mono-EPCs treatment did not result in any improvement in alveolar structure could be due to the selected route of administration.…”
Section: Combined Epc Transplantation and Ino Improved Lung Structurementioning
confidence: 74%
See 1 more Smart Citation
“…However, in this study, we found that in the late phase of BPD, a single dose of EPCs administered through the peripheral venous route only increased lung microvessels, with no improvement in alveolar structure as determined by RAC measurements. Compared with the two previous studies (9,10), the reason why mono-EPCs treatment did not result in any improvement in alveolar structure could be due to the selected route of administration.…”
Section: Combined Epc Transplantation and Ino Improved Lung Structurementioning
confidence: 74%
“…Balasubramaniam et al (9) showed that bone marrow-derived angiogenic cells injected into the pulmonary circulation can restore lung alveolar and vascular structure after neonatal hyperoxia in infant mice. Grisafi et al (10) showed that amniotic fluid stem cells delivered intratracheally can restore partly alveolarization and angiogenesis in an adult rat model of hyperoxia lung injury. Although stem cell therapy is a promising novel therapy for vascular injury-related diseases, studies have demonstrated that only a small portion of transplanted cells can home to the target (11,12).…”
mentioning
confidence: 99%
“…Following implantation in rat and porcine animal models, there was partial replacement of gut function. 26,27,61,62 Even though there have been a number of studies studying the components, electrophysiology, immunology, angiogenesis and lymphangiogenesis of the TESI (for an overview of these, refer to Table 1 of Ref. 63), this methodology has been heavily criticised.…”
Section: Oesophagusmentioning
confidence: 98%
“…25 It is possible that AFS cells display a reparative potential through active involvement of cells in alveolarisation and angiogenesis in a rat model of hyperoxia. 26 Paracrine activity and direct contribution of the stem cells could become relevant in the near future and avoid the need of transplantation in severe CDH.…”
Section: Airwaysmentioning
confidence: 99%
“…Yet there has been no systematic review to assess the extent of current evidence regarding safety and efficacy of cell-based therapies in preclinical BPD and identify gaps that could jeopardize successful clinical translation. studies), [26][27][28][29]32,34,35,37,39,40,42,43,48,49,[51][52][53][55][56][57][58][59][61][62][63]66,[68][69][70]72,73,[75][76][77][78] human amniotic epithelial cells (hAEC, n = 4), 36,64,65,74 mononuclear CD34 + (n = 4), 27,30,46,47 endothelial colony forming cells (ECFC, n = 3), 46,64,70 endothelial progenitor cells (EPCs, n = 3), 31,41,71 bone marrow derived angiogenic cells (BMDAC, n = 1), 71 bone marrow derived (BM) ckit+ cells (n = 1), 50 cord blood CD34 + (n = 1), 44 human amniotic fluid stem cells (hAFSC, n = 1), 33 human-induced pluripotent...…”
Section: Significance Statementmentioning
confidence: 99%